2013
DOI: 10.1093/carcin/bgt372
|View full text |Cite
|
Sign up to set email alerts
|

Gas6/Axl pathway promotes tumor invasion through the transcriptional activation of Slug in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common fatal cancers worldwide. Other than the sorafenib treatment, no effective systemic therapy has been available thus far. Most targets in molecularly targeted therapy for cancer are receptor tyrosine kinases (RTKs). Therefore, identifying activated RTKs in HCC is critical for developing new molecularly targeted therapies. Using a phospho-RTK array, we found that Axl is one of the most frequently activated RTKs in liver cancer cell lines. The knockdown of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 34 publications
4
85
0
Order By: Relevance
“…Slug-induced expression of cyclin D1 was also reduced following suppression of Axl. Slug-mediated activation of ERK1/2 and JNK, which are downstream signaling molecules of Axl [29, 30], was reduced by knockdown of Axl (Figure 4H). A reporter assay showed that AP-1 activation by Slug was decreased by suppression of Axl (Figure 4I, upper).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Slug-induced expression of cyclin D1 was also reduced following suppression of Axl. Slug-mediated activation of ERK1/2 and JNK, which are downstream signaling molecules of Axl [29, 30], was reduced by knockdown of Axl (Figure 4H). A reporter assay showed that AP-1 activation by Slug was decreased by suppression of Axl (Figure 4I, upper).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Axl is upregulated by Slug and Snail in MCF10A immortalized breast epithelial cells and plays a critical role in breast cancer cell invasion [26], and Slug induces the expression of Axl among 49 receptor tyrosine kinases at the transcriptional level to activate Axl, which maintains Slug expression through a positive feedback loop [28]. In addition, the Gas6/Axl pathway upregulates Slug expression through MAPK [29, 51], suggesting a positive feedback loop between Slug and Axl during cancer progression. On the other hand, we previously reported that ZEB2 directly interacts/cooperates with Sp1 to function as a transcriptional activator of mesenchymal genes (vimentin, integrin α5, and cadherin-11) to induce invasion [53].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it has been studied in many conditions. Gas6 and TAM regulate cell growth and an overactivation of the system has been associated to several neoplastic conditions and proposed as a novel therapeutic target [37,38,39,40,41,42,43,44,45,46,47,48]. Furthermore, TAM receptors are involved in haemostasis.…”
Section: The Gas6/tam Receptors Systemmentioning
confidence: 99%
“…9,10 AXL is frequently overexpressed in human cancers including lymphocytic leukemia, breast, colon, skin, thyroid and prostate cancer. [11][12][13][14][15][16][17] Down-regulation of AXL by siRNA attenuates the migration and invasion of breast, 18 ovarian, 19 hepatocellular carcinoma, 20 mesothelioma, 21 prostate 22 and pancreatic cancer. 23 Furthermore it has been shown that the inhibition of AXL results in the reduction of cancer progression and metastatic potential and induces apoptosis in cancer cells.…”
Section: Introductionmentioning
confidence: 99%